Is molecular chirality connected to supramolecular chirality? the particular case of chiral 2-pyridyl alcohols - Tsang, Min Ying (2015)
Ten structurally related racemic 2-pyridylmethyl alcohols containing an o-carborane core (1,2-closo-C2B10H10; rac-1a) or m-carborane (1,7-closo-C2B10H10; rac-2a) or p-carborane (1,7-closo-C2B10H10; rac-3a) and their enantiopure forms (R- and S-1a or R- and S-2a or R- and S-3a), as well as an iodo derivative of rac-3a (rac-4a) and a non-carborane derivative (C6H5; rac-5) have been studied by single crystal X-ray crystallography. All racemic and enantiopure structures show O-H⋯N hydrogen bonded homochiral 21-helical networks, except that for rac-3a, which forms O-H⋯N hydrogen bonded trimers. A comparison of these X-ray structures with that for others found in the Cambridge Structural Database for chiral 2-pyridyl alcohols-either in racemic or enantiopure forms-that form O-H⋯N hydrogen bonded homochiral 21-helical networks reveals a possible relationship between the torsion angle of the hydrogen bond donor and acceptor groups in these molecules and the hydrogen bonded supramolecular helices formed in the solid state.